Robust H∞ containment control for nonlinear multi‐agent systems with intermittent communication. (3rd December 2021) - Tan, Manchun; Zhang, Xuemei; Ye, Lei; Lin, Peiqun
Abstract: This article investigates the H ∞ containment control problem for a general class of nonlinear multi‐agent systems under external disturbances with multileaders. A kind of intermittent protocol depending only on the relative local measurement of neighboring agents is put forward to analyze the effect of external disturbances for solving the containment control problem under directed topology. By adopting the intermittent control protocol and robust H ∞ control method, some sufficient conditions are derived to guarantee that all followers asymptotically converge to the convex hull spanned by all the leaders with the provided H ∞ performance index. Moreover, the unknown feedback matrix of the proposed control scheme is determined directly by solving only two linear matrix inequalities (LMIs) regardless of the number of all agents. Finally, a simulation example is given to illustrate the effectiveness of the theoretical analysis.